Fray José Lamana OP (ca. 1650-1715), cronista del Real Convento de Predicadores de Zaragoza en la época de los Austrias Menores. - LÓPEZ RIBAO, ALEJANDRO JOSÉ (Scripta, 2020)
Friar José Lamana (Borja ca. 1650 - Zaragoza 1715) was a dominican friar from the Royal Priory of Preachers of Zaragoza. After worked in different academic institutions, especially like rector of the College of San Jorge and Santo Domingo of Tortosa, dedicated his last years to being the librarian and chronicler of his convent. At that time, he wrote two Lumen Domus or convent chronicles. The first is preserved in the University Library of Zaragoza and the second, until now unidentified, in the Diocesan Archive of the same city. Both remain unpublished. The study of his figure, his work as a chronicler and the importance of his historiographical contribution is the main purpose of this article.